Determination of caffeine, chlorogenic acid and nicotinic acid in coffee beans by using HPLC / Nor Hanisah Mat Yassin - Mat Yassin, Nor Hanisah (Faculty of Applied Sciences, 2008)
Coffee usually comes in two types of coffee beans. They are coffee arabica and coffee robusta. These coffees contain many chemicals that are affected during the roasting process. The coffee contains caffeine, chlorogenic acid and nicotinic acid which give a variety of the effect that is both beneficial and harmful to human. This research will determine the amount of compound such as caffeine, chlorogenic acid and nicotinic acid present in coffee after roasting. The coffee beans were roasted in an oven and grounded coffee was brewed in freezer. The sample preparation was quite simple involving only heating water extraction and filtration. Analytical HPLC unit consists of Water 717 plus Autosampler and Water 600 Controller, Water 2487 Dual λ Absorbance detector, a 150 x 4.6 mm i.d. Merck Superspher 100 Reversed Phase (RP), C-18 column with 5 μm particle sizes. The analysis is uses reversed phase (RP) column with gradient elution of 10 mM citric acid (A) and methanol (B). Robusta coffee beans contained the highest amount of caffeine compared with arabica were, 36.0290 mg/ml and 35.2950 mg/ml respectively. The amount nicotinic acid in roasted coffee arabica for five minute was 0.5859 mg/ml and roasted coffee robusta was 0.7000 mg/ml. The amount of chlorogenic acid in brewed coffee samples is smaller than roasted coffee sample. In roasted coffee sample, the amount of CGA in arabica and robusta were 10.8936 mg/ml and 15.1398 mg/ml respectively. COPYRIGHT ©